Konstruksi Realitas Sosial-Budaya Etnis Tionghoa di Palembang: Studi Komunikasi Antar-Budaya - Aprilyanti Pratiwi (Fakultas Ilmu Komunikasi Universitas Pancasila, 2016)
As one of the ethnic groups in Indonesia, Chinese Indonesians groups often face discrimination from other ethnic groups in Indonesia. How Chinese ethnic groups in Palembang construct socio-cultural reality according to their own views? How do they manage their communications with the impression of local residents? The answer to these questions can be found through this qualitative study of Intercultural Communication by conducting interviews observations of the two informants, and data analysis of the articles of Kampung Kapitan. The results showed that the Chinese community of Kampung Kapitan assumed their villages is an ancestral heritage that must be protected not only their building but also their cultures too. The Chinese ethnic of Kampung Kapitan assumed that they are wong Plembang (Palembang people). The frequency of communications of Chinese ethnic community of Kampung Kapitan with surrounding communities where they live is very high. The process of acculturation and modernization of the Chinese ethnic of Kampung Kapitan are on marriage, religion, and values. Verbally, Chinese ethnic of Kampung Kapitan in general use Palembang language, non-verbally that the appearance and clothing as well as movement and posture are the same as that of Palembang ethnic communities. The obvious between Chinese ethnic groups of Kampung Kapitan people and Palembang people are paler skin and slit eyes.